Impact of Improper Approach to Identify Lid Wiper Epitheliopathy (LWE) - Lievens CW (Dove Medical Press, 2020)
Christopher W Lievens,1 Yvonne Norgett,2 Nancy Briggs,3 Peter M Allen,4 Marta Vianya-Estopa2 1The Eye Center, Southern College of Optometry, Memphis, TN, USA; 2Department of Vision & Hearing Sciences, Anglia Ruskin University, Cambridge, UK; 3Mark Wainwright Analytical Centre, University New South Wales, Sydney, Australia; 4Vision and Eye Research Unit, Anglia Ruskin University, Cambridge, UKCorrespondence: Christopher W LievensThe Eye Center, Southern College of Optometry, 1245 Madison Avenue, Memphis, TN 38104, USATel +1 901 722 3330Fax +1 901 722 3280Email clievens@sco.eduPurpose: Variability in the use of ophthalmic dyes to diagnose lid wiper epitheliopathy (LWE) has led to division in the literature and clinical practice. The principal aim of this study was to evaluate whether the use of a non-optimal methodology to identify LWE had a potential for false negatives; in which LWE was overlooked.Patients and Methods: A total of 20 participants were initially categorized to not have LWE and were enrolled in this study. The protocol examined whether or not LWE would later be revealed through the use of optimized methodology. Semi-automated analysis was performed of images taken after two different drop instillations with varying post-dye viewing times for both lissamine green (LG) and sodium fluorescein (NaFl).Results: There was a significant increase in area of staining revealed when an optimal methodology for LWE identification was used. Comparisons for every non-optimal condition were statistically significantly different against the optimal condition (all p< 0.01). The use of a non-optimal methodology resulted in a 70% false-negative rate when using LG and a 95% false-negative rate when using NaFl.Conclusion: The study demonstrated that using a double instillation of dye was statistically different from a single-dose, even with extended wait time for clinical observation. A single instillation did not offer adequate volume of dye for adequate lid margin uptake. A careful adherence to volume as well as a repeat administration is key to revealing the full area of LWE. A non-optimal approach to diagnose LWE can lead to false negatives.Keywords: lid wiper, epitheliopathy, dry eye, lissamine green, sodium fluorescein, false negative